2000
DOI: 10.1023/a:1009898107964
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Heart failure is characterized by an elevation in sympathetic tone. The mechanisms responsible for this sympatho-excitation of heart failure are not completely understood. Several studies from this laboratory have compared differences in the cardiac "sympathetic afferent" reflex between sham dogs and dogs with pacing-induced heart failure. We found 1) that the cardiac sympathetic afferent reflex is augmented in heart failure, 2) tonic cardiac sympathetic afferent inputs play an important role in the elevated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…One potential explanation is an increased CSAR control of cardiac sympathetic efferent outflow (also called the “cardiac-cardiac reflex”) in CHF. It is well known that myocardial ischemia releases large amounts of metabolites including bradykinin, ATP, prostaglandins and protons that stimulate cardiac sympathetic afferent nerve endings and cause an excitatory response of MAP, HR and sympathetic nerve activity 1, 3, 4 . Previous studies from this laboratory 1, 2 demonstrated that acute epicardial application of lidocaine, which blocked cardiac sympathetic afferent input, decreased baseline MAP, HR and RSNA in anesthetized CHF dogs and rats but not in sham animals, indicating that the CSAR is tonically activated and contributes to the elevated renal sympathetic nerve activity in CHF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential explanation is an increased CSAR control of cardiac sympathetic efferent outflow (also called the “cardiac-cardiac reflex”) in CHF. It is well known that myocardial ischemia releases large amounts of metabolites including bradykinin, ATP, prostaglandins and protons that stimulate cardiac sympathetic afferent nerve endings and cause an excitatory response of MAP, HR and sympathetic nerve activity 1, 3, 4 . Previous studies from this laboratory 1, 2 demonstrated that acute epicardial application of lidocaine, which blocked cardiac sympathetic afferent input, decreased baseline MAP, HR and RSNA in anesthetized CHF dogs and rats but not in sham animals, indicating that the CSAR is tonically activated and contributes to the elevated renal sympathetic nerve activity in CHF.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that myocardial ischemia causes the production and release of several metabolites including bradykinin, prostaglandins and protons that stimulate sympathetic afferent nerve endings leading to increases in arterial pressure (AP), heart rate (HR) and sympathetic nerve activity 1, 3, 4 . In CHF, the CSAR is sensitized and cardiac sympathetic afferents are tonically activated 1-3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to ASIC channels in skeletal muscle afferents, we have demonstrated that the ASIC channel in mouse cardiac afferents is a heteromer composed of ASIC2a and −3 subunits (Hattori et al, 2009). Besides serving as pain sensors during myocardial ischemia or infarction, cardiac sympathetic afferents trigger sympathoexcitation (Malliani et al, 1969; Minisi and Thames, 1991), and there is evidence to support their contribution to the detrimental sympathetic activation associated with cardiovascular disease states (Wang and Ma, 2000; Wu et al, 2008). …”
Section: Asics In Other Neural Pathways That Influence Cardiovascumentioning
confidence: 99%
“…Interaction between SNS and ANG II was demonstrated by several functional studies which showed that ANG II stimulates sympathetic neurotransmitter (NE) release by activation of its specific AT1 receptor (AT1R) located on presynaptic SNS terminal axon reaching cardiovascular tissues (Saxena, 1992;Cox et al 1995;Dendorfer et al 1998;Wang and Ma 2000). Moreover, the blockage of ANG II receptor AT1R with losartan reduces NE release and enhances its reuptake by SNS terminal axon (Raasch et al 2004).…”
Section: Introductionmentioning
confidence: 99%